New Perspectives on Goffman in Language and Interaction Body, Participation and the Self - Mondada, Lorenza; Peräkylä, Anssi (Taylor & Francis, 2024)
This collection highlights new perspectives on the work of Erving Goffman, revisiting his place in contemporary social theory and interactional linguistics research and its impact in surfacing new insights in conversation analysis and our understanding of Goffman's legacy. The volume outlines the theoretical foundations of Goffman's research across linguistics and the social sciences. Bringing together a crossdisciplinary group of scholars, the book is organized around these themes, with sections on self and identity, participation, and bodily practices in social interaction. Each chapter comprises three perspectives- look back at Goffman's original texts, their correlation in contemporary empirical research in conversation analysis, and a discussion of conceptual implications in relevant fields such as interactional sociolinguistics, linguistic anthropology, critical sociolinguistics, and related disciplines. Taken as a whole, the book not only offers a comprehensive critical overview of Goffman's legacy in empirical work in conversation analysis and the social sciences but also the conceptual grounding for new studies to investigate his continuing role in contemporary scholarship. This innovative collection will be of interest to students and scholars in sociolinguistics, linguistic anthropology, and critical discourse analysis as well as sub-disciplines of sociology and psychology.